N-doped MgZnO alloy thin film prepared by sol-gel method - Chongsri, K.; Boonruang, S.; Techitdheera, W.; Pecharapa, W. (My University, 2011)
In this work, nitrogen-doped MgZnO thin films were deposited on glass substrate by spin-coating technique and thermal annealing treatment. The X-ray diffraction (XRD), scanning electron microscope (SEM) and optical transmission measurement were carried out to investigate the effect of growth temperature and nitrogen doping on the physical and optical properties of the films. XRD and SEM results revealed that the crystallinity and preferred c-axis orientation was enhanced with increasing annealing temperature and certain concentration of N-doping. In addition, the films incorporated with nitrogen doping exhibit significant blue shift in optical band gap and improvement in its transparency. © 2011 Elsevier B.V. All rights reserved.
Keywords: MgZnO; N-doping; Sol-gel method